Trust management for reliable decision making among social objects in the Social Internet of Things. Issue 4 (1st July 2017) - Meena Kowshalya, A.; Valarmathi, M.L.
Abstract : The Internet is populated with billions of electronic gadgets that have become a part of our fabric. Internet of Things is gaining popularity in at most all applications from smart buildings, intelligent transportation, healthcare and defence. IoT is a many vision one paradigm technology. One of the many visions of IoT is to make 'Things' social. Social Internet of Things (SIoT) is a young paradigm that integrates IoT and Social networking principles where Things are not only autonomous and smarter but also socially conscious. The authors propose a trust management scheme to facilitate trustworthy automatic decision making based on behaviour of objects. The authors use SIoT Trust metrics namely direct trust, centrality, community interest, Cooperativeness, Service Score to compute Trustworthiness among objects. The Expected trust and periodic trust updates evidently identify the presence of 'on off' selective forwarding attacks. The authors demonstrate the advantages of the proposed scheme with other existing trust management schemes in the literature.